Contribution of EARLINET/ACTRIS to the summer 2013 Special Observing Period of the ChArMEx project: monitoring of a Saharan dust event over the western and central Mediterranean. Issue 19 (1st October 2016) - Sicard, M.; Barragan, R.; Muñoz-Porcar, C.; Comerón, A.; Mallet, M.; Dulac, F.; Pelon, J.; Alados Arboledas, L.; Amodeo, A.; Boselli, A.; Bravo-Aranda, J. A.; D'amico, G.; et al.
ABSTRACT: In the framework of the Chemistry-Aerosol Mediterranean Experiment (ChArMEx; http://charmex.lsce.ipsl.fr/ ) initiative, a field campaign took place in the western Mediterranean Basin between 10 June and 5 July 2013 within the ADRIMED (Aerosol Direct Radiative Impact on the regional climate in the MEDiterranean region) project. The scientific objectives of ADRIMED are the characterization of the most common 'Mediterranean aerosols' and their direct radiative forcing (column closure and regional scale). During 15–24 June a multi-intrusion dust event took place over the western and central Mediterranean Basin. Extra measurements were carried out by some EARLINET/ACTRIS (European Aerosol Research Lidar Network /Aerosols, Clouds, and Trace gases Research InfraStructure Network, http://www.actris.net/ ) lidar stations in Spain and Italy, in particular on 22 June in support to the flight over southern Italy of the Falcon 20 aircraft involved in the campaign. This article describes the physical and optical properties of dust observed at the different lidar stations in terms of dust plume centre of mass, optical depth, lidar ratio, and particle depolarization ratio. To link the differences found in the origin of dust plumes, the results are discussed on the basis of back-trajectories and air- and space-borne lidars. This work puts forward the collaboration between a European research infrastructure (ACTRIS) and an international project (ChArMEx) on topics of interest for both parties, and more generally for the atmospheric community.